2014
DOI: 10.1186/1880-5981-66-25
|View full text |Cite
|
Sign up to set email alerts
|

Wide-angle refraction experiments in the Daito Ridges region at the northwestern end of the Philippine Sea plate

Abstract: Three large bathymetric highs (from north to south: the Amami Plateau, the Daito Ridge, and the Oki-Daito Ridge) originating from paleo-island arcs characterize the northwestern end of the Philippine Sea plate. We obtained 10 seismic refraction and multi-channel seismic reflection profiles across and along these bathymetric highs and obtained P wave velocity (Vp) models of the crust and the uppermost mantle. Although there are large variations in the crustal structure throughout this region, these bathymetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…The slightly low V p of 7.6 km/s in the uppermost mantle along the southeastern end of ECr11 is same as the upper mantle velocity beneath the Amami Plateau obtained by Nishizawa et al (2014). The Pn velocity at northern end of DAr5, to the east of ECr11, is slightly higher V p of 7.8-8.0 km/s (Nishizawa et al 2014), which indicates less influence of the Amami Plateau.…”
Section: Subduction Of the Philippine Sea Platesupporting
confidence: 50%
See 2 more Smart Citations
“…The slightly low V p of 7.6 km/s in the uppermost mantle along the southeastern end of ECr11 is same as the upper mantle velocity beneath the Amami Plateau obtained by Nishizawa et al (2014). The Pn velocity at northern end of DAr5, to the east of ECr11, is slightly higher V p of 7.8-8.0 km/s (Nishizawa et al 2014), which indicates less influence of the Amami Plateau.…”
Section: Subduction Of the Philippine Sea Platesupporting
confidence: 50%
“…The slightly low V p of 7.6 km/s in the uppermost mantle along the southeastern end of ECr11 is same as the upper mantle velocity beneath the Amami Plateau obtained by Nishizawa et al (2014). The Pn velocity at northern end of DAr5, to the east of ECr11, is slightly higher V p of 7.8-8.0 km/s (Nishizawa et al 2014), which indicates less influence of the Amami Plateau. In the southern seismic lines of the Ryukyu Trench, Pn velocities in the southeastern end of the ECr7 and ECr6 are 7.7-7.9 and 7.8 km/s, respectively, which are slightly smaller than ~8.0 km/s obtained in the Shikoku Basin, the backarc basin on the PHS plate to the east (Nishizawa et al 2011).…”
Section: Subduction Of the Philippine Sea Platesupporting
confidence: 50%
See 1 more Smart Citation
“…1) are also originated from paleo-island arcs. Nishizawa et al (2014) showed that these bathymetric highs usually have a middle crust with a Vp of 6.3-6.8 km/s, a lower crust with Vp = 6.8-7.2 km/s, a Pn velocity of 7.6-7.8 km/s, and a crustal thickness of 15-25 km. These structures are similar to those of the IBM island arc, which are immature paleo-island arcs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Daito Ridges, other significant bathymetric highs characterizing the Philippine Sea plate, were comprehensively investigated geologically and geophysically under the CSS Project in Japan (e.g., Ishizuka et al 2013;Nishizawa et al 2014). Three large bathymetric highs, the Amami Plateau, the Daito Ridge, and the OkiDaito Ridge, from north to south (Fig.…”
Section: Introductionmentioning
confidence: 99%